2017
DOI: 10.1111/ecog.03111
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal scaling of plant species richness and functional diversity in a temperate semi‐natural grassland

Abstract: The accumulation of biodiversity in space and time has been modelled extensively using the species–area relationship and the species–time relationship, respectively. Recently, these models have been combined into time–area curves in order to investigate spatiotemporal scaling of species richness. This study expands on previous research by applying these spatiotemporal models to functional diversity. Understanding spatiotemporal dynamics of ecological traits is important due to their crucial role in ecosystem f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Herbivores, on the other hand, did not exhibit patterns of increasing or decreasing divergence from null with island area for phylogenetic diversity, as with functional diversity, despite a significant species–area relationship. This suggests that for herbivores at least, the spatial scaling of species richness may be separate from the scaling of other biodiversity dimensions (Mazel et al, ; White, Montgomery, Pakeman, & Lennon, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivores, on the other hand, did not exhibit patterns of increasing or decreasing divergence from null with island area for phylogenetic diversity, as with functional diversity, despite a significant species–area relationship. This suggests that for herbivores at least, the spatial scaling of species richness may be separate from the scaling of other biodiversity dimensions (Mazel et al, ; White, Montgomery, Pakeman, & Lennon, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, competitive assembly means that if habitat destruction reduces the carrying capacity of an island, biotic filters limit the similarity of any remaining species. Thus, competitive assembly may mean that functional and/or phylogenetic diversity is more resistant than species richness to disturbance (Mazel et al, ; White et al, ). Our finding that trophic levels were governed by different assembly mechanisms in the Ryūkyū archipelago suggests that we should consider differences in disassembly rules for these groups to best manage biodiversity of these islands in future.…”
Section: Discussionmentioning
confidence: 99%
“…Blonder et al (2018) found that paleoclimate (i.e., MAT and MAP) is a better predictor of the spatial pattern of contemporary functional plant composition than contemporary climate predictors. The spatial pattern of contemporary functional plant composition is related to the distribution of plant richness at large scales (Petchey & Gaston 2002, Thompson et al 2005, White et al 2018. Furthermore, plant species diversity may change more than functional-trait diversity because high levels of trait-based redundancy imply that the loss of a particular species should not affect ecosystem functions because of the maintenance of other species with similar traits (Dıáz & Cabido 2001, Petchey & Gaston 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that the mean and SD of leaf traits, such as LA and CC, can be predicted by temperature and precipitation. Annual precipitation and water vapor pressure are often interpreted as indicators of water availability, and temperature has a large contribution to the distribution and physiological performance of invasive plants from local communities to the global scale (Treurnicht et al 2016, Stark et al 2017, White et al 2018. Water availability has a high potential to affect leaf traits along temperature gradients (Leishman et al 2007, Messier et al 2017, and the negative relationship between LA variation and mean temperature is consistent with energy balance strategies (Leishman et al 2007, Stark et al 2017.…”
Section: Discussionmentioning
confidence: 99%